Boom-Bust Phases in Asset Prices and Fiscal Policy Behavior - Schuknecht, Ludger (IMF Working Papers; Working Paper ;, 2004)
Boom and bust phases in asset prices have become a pervasive feature of macroeconomic developments in many advanced economies. This paper studies fiscal policy during boom-bust phases in asset prices and draws several conclusions. First, expansions and contractions in economic activity during such boom-bust phases tend to be highly persistent, cyclical turning points are harder to forecast, and the margins of error for output gap estimates can be large. Second, conventional estimates of revenue elasticities seem not to allow an accurate assessment of the fiscal stance and of the strength of underlying fiscal positions during boom-bust phases. And third, boom-bust phases tend to exacerbate already existing procyclical policy biases, as well as political-economy biases, toward higher spending and public debt ratios.